Web-Based Infant Weight and Height Measurement for Early Stunting Detection at Krembangan Posyandu, Surabaya - Pudji, Andjar; Ridha Makruf, Muhammad; Priyambada Cahya Nugraha (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Early childhood is a critical phase for physical and cognitive development, making early detection of stunting vital to a child’s long-term health. Traditional methods of measuring infant growth in regions like Indonesia rely on manual data collection, leading to delays in identifying stunting. This study aims to implement a web-based system for infant weight and height measurements to assist healthcare workers in early stunting detection at Krembangan Posyandu, Surabaya. The system provides real-time monitoring, automatic z-score calculations, and data storage, enhancing efficiency and accuracy. Methodologically, the tool was tested with 16 infants, allowing cadres to input measurements directly into a web platform for analysis. Results showed the tool's ease of use, increased speed in data handling, and improved access to growth data, reducing manual errors. The findings indicated that most infants had healthy growth, though a few required further attention. In conclusion, this web-based tool significantly improves the accuracy and timeliness of stunting detection, with implications for wider adoption in regions with limited healthcare infrastructure. However, limitations include a small sample size and a lack of assessment of long-term outcomes. Future research should focus on larger populations and the tool’s integration into broader healthcare systems